2018
DOI: 10.1002/adma.201802031
|View full text |Cite
|
Sign up to set email alerts
|

The Sub‐Nanometer Scale as a New Focus in Nanoscience

Abstract: Size is one of the central issues in nanoscience. The practical meaning of the term "sub-nanometric material (SNM)" requires two aspects: (1) its size should be at the atomic level; (2) it shows unique (size-related) properties compared to its nano-counterparts with larger sizes. Here, SNMs in the form of wires (SNWs) and the unique properties arising from their special size are reviewed. First, their polymer-like behavior, including rheological behavior and self-assembly, is dicussed. Their origins may stem f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 194 publications
(244 reference statements)
0
94
0
1
Order By: Relevance
“…We observed that the generated he NBs were inclined to bend, twist, entangle, and form large bundles ( Figure 2, Supporting Information Figure S10). These observations might be due to the flexible nature of these sub-nanometric materials, 8 Figure S11), which suggested that the exposed basal planes were {110} facets, identical to those in eePtPd NBs. However, while {111} reflections were found in the Pd(0.9) NBs, 1/3(422) fringes were absent in the corresponding FFT patterns (Figure 2h, i) Thus we inferred that their exposed lateral facets could be {110}.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We observed that the generated he NBs were inclined to bend, twist, entangle, and form large bundles ( Figure 2, Supporting Information Figure S10). These observations might be due to the flexible nature of these sub-nanometric materials, 8 Figure S11), which suggested that the exposed basal planes were {110} facets, identical to those in eePtPd NBs. However, while {111} reflections were found in the Pd(0.9) NBs, 1/3(422) fringes were absent in the corresponding FFT patterns (Figure 2h, i) Thus we inferred that their exposed lateral facets could be {110}.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, the large ΔG tot difference of different nanocrystal morphologies would compensate for ΔG* if such a 1D structure could not be well-stabilized under proper conditions. We were able to satisfy the criterion by introducing ascorbic acid (AA), PVP, Hexacarbonylmolybdenum [Mo(CO) 6 , or dicobalt octacarbonyl [Co 2 (CO) 8 ] as a carbon monoxide (CO) source instead of CO gases, to ensure safety, and ethylenediamine (EN) into the synthesis. Mo(CO) 6 or Co 2 (CO) 8 release CO molecules at appropriate temperatures, which could be influenced by the reaction environment, such as water or ligands.…”
Section: Controlled Experiments For the Synthesis Of Pd(09) Nbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subnano films allow a more efficient use of resources, and do not affect the geometry of even high-aspect-ratio nanostructured substrate materials (3). Furthermore, the controlled growth of subnano films may allow the fabrication of novel materials with unprecedented properties for several potential applications in energy conversions such as electrocatalysis and photocatalysis (4). Organic coatings are of interest due to the advantages they hold over their inorganic analogues, such as biocompatibility (5,6), lower raw material costs, and reduced environmental impact (7).…”
Section: Introductionmentioning
confidence: 99%